A rare case of leiomyoma arising from a uterine remnant in a patient with Mayer–Rokitansky–Küster–Hauser syndrome - Inderpreet Kaur; Aishwarya Kapur; Anu Aggarwal; Sharda Patra; Reena Yadav (Current Medicine Research and Practice, 2025)
Mayer–Rokitansky–Küster–Hauser (MRKH) syndrome, a congenital disorder characterised by uterine and upper vaginal agenesis, rarely presents with leiomyomas in uterine remnants. We report the case of a 36-year-old woman with MRKH who presented with an abdominopelvic mass initially suspected to be an ovarian tumour. Laparotomy revealed that the mass originated from the right uterine remnant, which was histopathologically confirmed as a leiomyoma. This case highlights the diagnostic challenge of leiomyomas in patients with MRKH disease owing to the absence of a functional uterus, emphasising the need for a high index of suspicion and thorough imaging for accurate diagnosis and timely surgical intervention.